Production of Conjoined Transgenic and Edited Barley and Wheat Plants for Nud Genes Using the CRISPR/SpCas9 System - Zang, Yiming; Gong, Qiang; Xu, Yanhao; Liu, Huiyun; Bai, Hao; Li, Na; Du, Lipu; Ye, Xingguo; Lan, Caixia; Wang, Ke (Frontiers in Genetics, 2022)
The Nudum (Nud) gene controls the caryopsis type of cereal crops by regulating lipid biosynthetic pathways. Based on the HvNud sequence and its homologous gene sequences in wheat, a conserved sgRNA was designed to obtain the mutants from the barley variety ‘Vlamingh’ and the wheat variety ‘Fielder’ via Agrobacterium-mediated transformation. A total of 19 and 118 transgenic plants were obtained, and 11 and 61 mutant plants were identified in T0 transgenic plants in barley and wheat after PCR-RE detection, and the editing efficiencies of the targeted gene were 57.9% and 51.7% in barley and wheat, respectively. The grain shape of the barley mutants was naked. Five different combinations of mutations for wheat TaNud genes were identified in T0 generation, and their homozygous edited plants were obtained in T1 generation. Interestingly, the conjoined plants in which one plant has different genotypes were first identified. The different tillers in an individual T0 plant showed independent transgenic or mutant in both barley and wheat, and the different genotypes can stably inherit into T1 generation, indicating the T0 transgenic plants were conjoined type. In addition, we did not find any off-target mutations in both barley and wheat. A candidate method for detecting putative edited wheat plants was suggested to avoid losing mutations in this investigation. This study provides not only materials for studying the function of Nud gene in barley and wheat but also a system for detecting the mutants in wheat.